Hybrid carbon nanotube/polymer heterointerface organic field effect transistor - Chua, C.L.; Yeoh, K.H.; Woon, K.L. (Elsevier, 2014)
Hybrid carbon nanotube/polymer heterointerface field effect transistor is developed by drop-casting carbon nanotubes on top of the semiconducting polymer. This method results in enhancement of mobility by a factor of 10 compared with the control device. In contrast with most devices that integrating carbon nanotubes into the polymer, the on/off ratio of our device actually improves. The enhancement of on/off ratio is interpreted as a result of density of carbon nanotube approaching the percolation threshold. We show that such improvement can be possible only when the charge carriers travel throughout the bulk of the active layer.